Expert system development process of Integrated Disaster Management system for lead responding agency in Malaysia during response and early recovery phases / Khairilmizal Samsudin … [et al.] - Samsudin, Khairilmizal; Hussin, Mohamad Fahmi (Dr.); Mohd Yassin, Ahmad Ihsan; Kasri, Mohd Haikal; Hussain, Abdul Razak (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
The availability of experts during disaster response and recovery shall increase the capability and capacity of disaster management process. Challenges is that experts may not always be available all the time. Hence, an expert system such as Integrated Disaster Management System (IDMS) need to be developed in assisting emergency responders in managing disasters. Several models is available in developing an expert system, however it is found that each of this model is used to develop their own specific expert system causing it to be non-feasible for development of IDMS based on criteria of a computerized system for lead responding agency in Malaysia. Hence, it is the objective of this paper to outline the expert system development process of IDMS. Using document review and analysis method, four (4) past expert system development model were studied and analyzed. By comparing and understanding the four (4) past models, a seven (7) step expert system development process of IDMS is introduced which as the same time fulfilling the criteria of a computerized system for lead responding agency in Malaysia. It is the researcher's hope that the newly introduced Expert System Development Process will be utilized by other developers in future development of other expert system.